Correlation of Vitamin D with Obesity Parameters in Patients of Cardiometabolic Syndrome - Usman, Robina; Khattak, Munaza; Haq, Momina; Khattak, Madiha; Parveen, Tahira; Basharat, Tayaba (ADVANCES IN BASIC MEDICAL SCIENCES, 2020)
Objective: To find out the correlation between Vitamin D and obesity parameters in patients of cardiometabolic syndrome (CMS). Methodology: This case control study was carried out in Endocrinology Unit, Hayatabad Medical Complex Peshawar from January to April 2012 on hundred (fifty cases and fifty controls each) adult patients of CMS using purposive sampling. Controls were gender and age matched relatives of patients. Lipid profile, fasting blood sugar, blood pressure, waist circumference, height and weight (to calculate Body Mass Index) were recorded. Serum levels of 25(OH) D were analysed by ELISA. Results: Mean values of cases for Body Mass Index (BMI), Waist Circumference (WC) and Waist Hip Ratio (WHR) were 30.30±4.60 kg/m2, 103.48±4.27 cm, 1±2.28 whereas in controls, the mean values came out to be 22.77±1.85 kg/m2, 81.56±7.77 cm, 0.82±1.94 respectively. In cases and controls, Vitamin D3 levels were 15.03±18.11 and 24.11±17.05 ng/ml respectively. A statistically significant negative correlation was identified between vitamin D and waist circumference (r = -.205; p=0.04) and vitamin D and waist hip ratio (r = -.213; p=0.03). Conclusion: Our results suggest that high WC and WHR are likely to be inversely correlated with hypovitaminosis D. Keywords: Waist Circumference, 25(OH)D, Waist Hip Ratio, Cardiometabolic Syndrome, BMI